Association Between Unaided Speech Perception in Noise and Hearing Aid Use Mediated by Perceived Benefit - Anthony Marcotti; Catherine Silva-Letelier; Javier Galaz-Mella; Alejandro Ianiszewski; Nicole B. Vargas; Eduardo Fuentes-López (Audiology Research)
Background/Objectives: The conventional strategy for addressing age-related hearing loss is hearing aid (HA) use, yet many individuals underutilize their devices. Despite the positive effects of HA use, adherence remains low, highlighting the importance of studying associated variables. We hypothesize that better unaided speech perception in noise (SPiN) would be associated with greater perceived benefit from HAs, which, in turn, would be linked to increased HA use. Methods: A cross-sectional study design was used, including 114 older adults (≥65 years) who were HA users. HA use and perceived benefit were assessed using questions 1 and 2 of the International Outcome Inventory for Hearing Aids (IOI-HAs), while unaided SPiN performance was measured monaurally with a speech-in-noise test. In the mediation analysis, SPiN performance was the predictor, perceived benefit the mediator, and HA use the outcome. Direct and indirect effects were evaluated using generalized structural equation modeling. Results: No significant total effect was found for the right ear. For the left ear, there was a significant indirect effect of SPiN performance on HA use through perceived benefit (OR = 1.26, 95% CI 1.06–1.57, p = 0.019) but no direct effect (p = 0.563). In addition, a significant total effect of left ear SPiN performance on HA use was observed (p = 0.041). Conclusions: The findings suggest that unaided SPiN performance—particularly in the left ear—may be indirectly associated with HA use through its effect on perceived benefit. These results underscore the potential value of including SPiN assessments in the HA fitting process and counseling strategies for older adults.